2014
DOI: 10.1002/2014gl060509
|View full text |Cite
|
Sign up to set email alerts
|

A one‐parameter Budyko model for water balance captures emergent behavior in darwinian hydrologic models

Abstract: Hydrologic models can be categorized as being either Newtonian or Darwinian in nature. The Newtonian approach requires a thorough understanding of the individual physical processes acting in a watershed in order to build a detailed hydrologic model based on the conservation equations. The Darwinian approach seeks to explain the behavior of a hydrologic system as a whole by identifying simple and robust temporal or spatial patterns that capture the relevant processes. Darwinian-based hydrologic models include t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
237
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 248 publications
(243 citation statements)
references
References 44 publications
5
237
0
1
Order By: Relevance
“…We finally obtained the mean of the 1000 combinations of R 2 and p values to determine the attributes that could best explain the residual effect. The assumption of steady-state conditions (dS/dt ≈ 0) of the Budyko framework required to maintain the constant water supply limit may also become a potential source of uncertainty for calculations of (E/P ) r (Chen et al, 2013;Greve et al, 2016;Wang and Tang, 2014;. It is possible that a time interval of 1 year may not guarantee stationary conditions (i.e.…”
Section: Regression Analysis Of the Residual Effect And Forest Attribmentioning
confidence: 99%
“…We finally obtained the mean of the 1000 combinations of R 2 and p values to determine the attributes that could best explain the residual effect. The assumption of steady-state conditions (dS/dt ≈ 0) of the Budyko framework required to maintain the constant water supply limit may also become a potential source of uncertainty for calculations of (E/P ) r (Chen et al, 2013;Greve et al, 2016;Wang and Tang, 2014;. It is possible that a time interval of 1 year may not guarantee stationary conditions (i.e.…”
Section: Regression Analysis Of the Residual Effect And Forest Attribmentioning
confidence: 99%
“…The parameter b is the maximum value of Y t . Wang and Tang (2014) demonstrated that Eq. (9) S t is controlled by the assumption that the loss rate of actual evaporation from soil water storage is proportional to the evapotranspiration capacity.…”
Section: A Monthly Water Balance Model: Abcd Modelmentioning
confidence: 99%
“…It is widely used and well-established within the hydrological community, due both to its simplicity and long history, combining experience from over a century of hydrological research. Budyko (1958Budyko ( , 1974 derived a formulation of the function based on findings of Schreiber (1904) and Ol'Dekop (1911), and several other formulations have also been postulated which are numerically very similar (Schreiber, 1904;Ol'Dekop, 1911;Turc, 1954;Mezentsev, 1955;Pike, 1964;Fu, 1981;Choudhury, 1999;Zhang et al, 2001Zhang et al, , 2004Porporato et al, 2004;Yang et al, 2008;Donohue et al, 2012;Wang and Tang, 2014;. Many of these formulations are empirically derived and only few are analytically determined from simple phenomenological assumptions (Fu, 1981;Milly, 1994;Porporato et al, 2004;Zhang et al, 2004;Yang et al, 2007; S. .…”
Section: Introductionmentioning
confidence: 99%